PENERAPAN APLIKASI DUOLINGO UNTUK MENINGKATKAN KEMAPUAN MENYIMAK BAHASA ARAB SISWA KELAS II MI MIFTAHUL JANNAH T.A 2023/2024 - Viny Rias Anggraini; Fauzana Annova (CV. ADIBA ASIHA AMIRA, 2024)
The use of Duolingo application is one of the alternatives that can be used in language learning, one of which is Arabic listening learning. This study aims to describe the learning process by using the Duolingo application. As a learning media. The method used in this research is qualitative descriptive method. This research was conducted at an Integrated Islamic Primary School in Padang class involving 35 students. Data were obtained from observation and student interviews. Based on the results of the study, it can be concluded that the learning process through the duolingo application can be used as an alternative for teachers to increase students' learning independence and practice listening skills This shows that the use of Duolingo can be an alternative media for learning Arabic.